ANALISIS AKUNTANSI DIFERENSIAL PADA PT CHAROEN POKPHAND INDONESIA Tbk - Sari, Ayu Indah; Ardelilla, Shabrina Ria; Fionasari, Dwi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2020)
ABSTRACT One of the functions of management is planning. Managers are faced with decisions regarding the selection of various types of alternatives. Every decision taken by management will be a measure of the success of a company in the future. One way to avoid mistakes in decision making is to use differential analysis. Where differential cost analysis is an approach to relevant cost analysis focused on different costs in a series of alternatives. The purpose of this research is to provide relevant information for business owners to determine what costs can arise from each alternative and compare to see the benefits generated between direct sales or products that are further prospecting. And from this study, business owners in developing their business by choosing alternatives to further process the product can be applied, because if the product is further processed, the revenue to be received is more profitable.